2020
DOI: 10.18848/2470-9247/cgp/v06i01/1-19
|View full text |Cite
|
Sign up to set email alerts
|

Digital Nationalism on Weibo on the 70th Chinese National Day

Abstract: China's digital nationalism has been on the rise during the last decade. This article examines the digital nationalistic expression of solidarity and unity on China's 70th National Day celebration in 2019. It conducted a qualitative content analysis of 500 posts regarding China's National Day, which were posted on October 1, 2019, on Sina Weibo. This study finds that Chinese internet users employ textual and visual posts to express their pride and loyalty, thereby reflecting their Chinese identity, a call for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Additionally, the media content is influenced by the Chinese communis t ideology. However, due to the influence of the market, the news content is also partially influenced by the liberal ideology in order to serve the public and commercial interests and to offer a public sphere for interaction (Ma, Webber, and Finlayson 2009;Zhang 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the media content is influenced by the Chinese communis t ideology. However, due to the influence of the market, the news content is also partially influenced by the liberal ideology in order to serve the public and commercial interests and to offer a public sphere for interaction (Ma, Webber, and Finlayson 2009;Zhang 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese media's voice highly aligns with that of the government (Zhao 2008). However, previous research also suggests that since the development of technology, the Chinese media has had more freedom to make public the news on environmental problems (Tong 2014;Zhang, Mol, and He 2016;Zhang 2020a). The research question that arises is 'To what extent is the news content on pollution in China produced under the influence of social systems?'…”
Section: Introductionmentioning
confidence: 99%
“…However, others are more skeptical, either because they believe that low-cost activities on social media will act as a replacement for real-world action ("slacktivism") or because they believe that authoritarian governments are becoming better at utilizing the same tools to suppress dissent (Morozov, 2012). Zhang (2020a) further posits that although viewed as liberal in the Chinese media environment, social media also follows the media logic that is dominated by the Chinese government. Overall, although the previous studies debate the role of social media in China, it widely accepts that social media in China could play a role as a public sphere to reach the public (Fang & Repnikova, 2018;Zhang, 2020b).…”
Section: The Media Environment In Chinamentioning
confidence: 99%
“…However, this article argues that it is insufficient to say that social media could help the think tanks break the boundary of Chinese Confucian culture and the "bureaucracy-oriented tradition." Zhang (2020a) proffers that although viewed as liberal in the Chinese media environment, social media still follows the traditional media logic that facilitates the government's interests. This study found the same pattern that although think tanks use social media to write articles and choose topics of discussion, they still need to follow the rule of Chinese Confucian culture and the "bureaucracyoriented tradition" promoted by the prevailing Chinese political power.…”
Section: Meanwhilementioning
confidence: 99%
See 1 more Smart Citation